PEMAKNAAN IKLAN BENG BENG VERSI PUTUS - Shaleh, Fadhly; Rimayanti, Nita (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The rapid advancement of technology in Indonesia, to make easy the process of information society. Television is a part of the development of communication technology that is able to provide a wide variety of information needed by the community. Electronic Media television also serves ads from different kinds of products. One of the products advertising on television is a popular advertising Beng Beng version of the break up, the ad is much liked by the people and become viral, and get awards bright awards 2016 category drama advertising bargains by being the winner in the nomination. This study aims to determine the meaning and messages contained in the ads Beng Beng version of the break up.This study used a qualitative descriptive approach. The method used in this research is the method of semiotic analysis, with the approach of semiotic analysis of Charles Sanders Peirce, by looking at the sign, object, and interpretan in Ad Beng Beng version broken.This research get result that the meaning of ad impressions Beng Beng version of the break up, Beng Beng has an important influence in a relationship. In addition, Beng Beng can be consumed wherever, whenever with the family, relatives, friends, and lover, so Beng Beng can be consumed by various age groups. Beng Beng made of a material that is very delicious and can be consumed directly or cooled first. Beng Beng gives pleasure that is not finite for the audience. So, they could forget everything and make Beng Beng as a priority.